Pelatihan Pembuatan Film pada Siswa SD dan SMP Taruna Islam Pekanbaru - Iik Idayanti; Adrian Aery Lovian; Ridwan (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2023)
Students in Taruna Islam's elementary and junior high schools, whose ages ranged from twelve to thirteen, were chosen as community service partners. The students on average come from middle to lower-economic families. This school is managed by the Islamic Taruna Foundation by employing twenty-four teachers, most of whom are honorary teachers. All teachers have not received certification. The facilities offered by this school are not many, however, the school's accreditation is very good with a grade of A. Based on daring investigations, there is little information about this school, such as student achievements and school activities. Responding to this condition can be interpreted that there are not many innovations for students that are carried out by this school, and this has an impact on the growth and development of children's creativity. In addition, with current technological developments, many children only use technology passively, rarely using technology to create positively and innovatively. The existing technology at home and school is less able to accommodate children's creativity. From this situation, we took the initiative to create activities to explore children's creativity in the form of film-making training. This service aims to make the film a medium that can be used as a space for students' creative aspirations and expressions by prioritizing Islamic values in their work. To achieve this goal, it is necessary to carry out a series of activities including (1) enrichment classes; (2) shooting (recording); (3) post-production; (4) movie screening.